Maternal nutritional status mediates the linkage between household food insecurity and mid-infancy size in rural Bangladesh - Na, Muzi; Shamim, Abu Ahmed; Mehra, Sucheta; Labrique, Alain; Ali, Hasmot; Wu, Lee S.-F.; Shaikh, Saijuddin; Klemm, Rolf; Christian, Parul; West, Keith P. (Cambridge University Press, 2022)
This article was published in The British Journal of Nutrition by Cambridge University Press [ Copyright © © The Authors 2020] and the definite version is available at: https://doi.org/10.1017/S0007114520000707 The Journal's website is at: https://www.cambridge.org/core/journals/british-journal-of-nutrition/article/maternal-nutritional-status-mediates-the-linkage-between-household-food-insecurity-and-midinfancy-size-in-rural-bangladesh/5FA83561E3B3C36E2AF3B67501F64B9F